2019
DOI: 10.1136/bmjopen-2018-026193
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating antibiotic stewardship in a tertiary care hospital in Kerala, India: a qualitative interview study

Abstract: ObjectivesTo determine what barriers and facilitators to antibiotic stewardship exist within a healthcare facility.Setting1300-bed tertiary care private hospital located in the state of Kerala, India.Participants31 semistructured interviews and 4 focus groups with hospital staff ranging from physicians, nurses, pharmacists and a clinical microbiologist.ResultsKey facilitators of antibiotic stewardship (AS) at the hospital included a dedicated committee overseeing appropriate inpatient antibiotic use, a prompt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Electronic Medical Record (EMR), Computerized Physician Order Entry (CPOE), Computer-assisted monitoring of antimicrobial prescriptions & hospital surveillance are among the IT activities performed. In agreement with our study, Baubie et al found that electronic medical record is an effective tool in an ASP [22].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Electronic Medical Record (EMR), Computerized Physician Order Entry (CPOE), Computer-assisted monitoring of antimicrobial prescriptions & hospital surveillance are among the IT activities performed. In agreement with our study, Baubie et al found that electronic medical record is an effective tool in an ASP [22].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, antibiogram was not performed in 51.4% hospitals, 17.1% reported updated antibiogram every year and 31.4% of the hospitals issued antibiogram on a 6 months interval basis. Baubie et al also reported updating hospital antibiogram annually by hospital microbiologist & clinical pharmacists [22].…”
Section: Discussionmentioning
confidence: 99%
“…Baubie et al . [ 21 ] identified that the presence of a microbiology laboratory, antibiogram, established guidelines for empiric prescribing, and committed leadership was important facilitators of an effective antibiotic stewardship program in a hospital. In Haryana, all 22 DHs have functional laboratories; however, well-equipped microbiology labs are functional in 12, and antibiograms are being generated in only 5.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Previous studies from low-and-middle-income countries (LMICs) have reported that patient demands often play a salient role in inconsistent prescription practices. [10][11][12][13][14][15] For example, Liu et al noted that rational prescribing practices are prone to weak control over prescribing behaviours, and 40% of prescriptions in a primary care setting in Hubei, China, contained an antibiotic, with 10% containing two or more antibiotics. 14 Where antibiotic stewardship efforts have worked, they have relied on dedicated committees overseeing antibiotic use, prompt laboratory investigations, established guidelines for empiric prescribing and an easily accessible antibiogram.…”
Section: Incomplete Intake Of Antibiotic Treatment and Explanatory Famentioning
confidence: 99%